BOSWELLIA SERRATA ROXB. – A BIOACTIVE HERBS WITH VARIOUS PHARMACOLOGICAL ACTIVITIES - MISHRA, SUDHANSHU; BISHNOI, RAM SINGH; MAURYA, RAHUL; JAIN, DEEPTI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Herbal medicine has become a medicinal as well as the economic aspect of global significance. While the use of these herbal medicines has increased, there are several questions about their consistency, protection, and effectiveness in different countries. Boswellic acid (BA) is one of the active constituents obtained from plant Boswellia serrata (BS) family Burseraceae. The oleoresin gum of the plant is also known as Salai guggul, Indian olibanum, or Indian frankincense. Boswellia species comprises a variety of phytochemical components, essential oil, BA such as keto-BA, beta-BA, or acetyl keto-BA. This variety of constituents isolated from the plant using various extraction processes such as hydrodistillation, percolation, and ultraviolet-assisted extraction or solvent extraction. The active constituent has different biological activities such as antidiuretic, anticancer, anti-inflammatory, or antitumor activity. This review seeks to update information on plant BS with its medicinal uses, isolation process in the traditional or Indian system of medicine, and justify its use on modern scientific parameters.